The book of form and emptiness eaudiobook A novel. - Ozeki, Ruth (Penguin Audio, 2021)
Winner of the Women’s Prize for Fiction “No one writes like Ruth Ozeki—a triumph.” —Matt Haig, New York Times bestselling author of The Midnight Library “Inventive, vivid, and propelled by a sense of wonder.” — TIME “If you’ve lost your way with fiction over the last year or two, let The Book of Form and Emptiness light your way home.” —David Mitchell, Booker Prize-finalist author of Cloud Atlas A boy who hears the voices of objects all around him; a mother drowning in her possessions; and a Book that might hold the secret to saving them both—the brilliantly inventive new novel from the Booker Prize-finalist Ruth Ozeki One year after the death of his beloved musician father, thirteen-year-old Benny Oh begins to hear voices. The voices belong to the things in his house—a sneaker, a broken Christmas ornament, a piece of wilted lettuce. Although Benny doesn't understand what these things are saying, he can sense their emotional tone; some are pleasant, a gentle hum or coo, but others are snide, angry and full of pain. When his mother, Annabelle, develops a hoarding problem, the voices grow more clamorous.   At first, Benny tries to ignore them, but soon the voices follow him outside the house, onto the street and at school, driving him at last to seek refuge in the silence of a large public library, where objects are well-behaved and know to speak in whispers. There, Benny discovers a strange new world. He falls in love with a mesmerizing street artist with a smug pet ferret, who uses the library as her performance space. He meets a homeless philosopher-poet, who encourages him to ask important questions and find his own voice amongst the many.   And he meets his very own Book—a talking thing—who narrates Benny’s life and teaches him to listen to the things that truly matter.   With its blend of sympathetic characters, riveting plot, and vibrant engagement with everything from jazz, to climate change, to our attachment to material possessions, The Book of Form and Emptiness is classic Ruth Ozeki—bold, wise, poignant, playful, humane and heartbreaking.